BPMN diagram dataset: Comprehensive collection of functional requirements - Sholiq Sholiq; Muhammad Ainul Yaqin (Data in Brief, 2024)
The dataset in this paper explains the functional requirements in the form of Business Process Modelling Notation (BPMN) diagrams from three software applications: employee cooperative, store, and mini hospital. Data were collected from clients or owners of software in three business software projects developed by development teams (including the authors) through requirements elicitation activities. The functional requirements are presented as a BPMN diagram. There are 67 data objects, each presenting a single functional requirement or process. Apart from being presented in diagram form, the BPMN diagram of the functional requirements is also provided in the form of an XML Process Definition Language (XPDL) file, making it possible for users of this dataset to export it using business process management platform tools. Due to the rarity of functional requirements presented in the form of BPMN diagrams for research and education, this dataset plays an important role in research and education in the fields of requirements engineering, software engineering, software metrics, business process modelling, and other relevant fields.